Respostas

A melhor resposta!
2014-04-27T14:48:17-03:00
A) y=1 e x=3 logo,           y = ax+b                     b) y= 4                              y= ax+b
                                      y = 3*3+8                       x= -4                             y= -1 *(-4)+0
a= Δy = 3 = 3                  y = 17                            a = Δy= 4 / -4 = -1         y= 4
    Δx    1                                                                   Δx
y= ax+b                                                                 y= ax+b
1 = 3*3+b                                                               4= -1 *(-4) +b
b = 9-1                                                                   4= 4+b
b = 8                                                                      b= 4 - 4 = 0
2 5 2